Dynamics and control for in-space assembly robots with large translational and rotational maneuvers - Zhang, Xianliang; Zhu, Weibing; Wu, Xiande; Song, Ting; Xie, Yaen; Zhao, Han (Acta astronautica, 2020)
There are two major characteristics of in-space structure assembly missions. First, in order to improve the transport efficiency of assembly robot and reduce the number of structural modules, the size of each structural module is usually designed as large as possible. Second, it is necessary for autonomous assembly robot to quickly transport such large-sized flexible structural modules to the desired locations for integration. However, the coupling effect between the deformation of structural module and large-scale maneuver of robot is inevitably involved during transportation. In this paper, a dynamics modeling method for in-space assembly (ISA) robot with large translational and rotational maneuvers was proposed. The descriptions of dual quaternions were expanded, and a general expression for the dynamics model of rigid-flex system was derived to describe motion of the assembly robot. Innovation of this method is that it considered the complex coupling effect among deformation of structural modules, translational and rotational maneuvers of the assembly robot during transportation in ISA missions. On this basis, the proportional-derivative (PD) controllers were adopted as the in-space structural module assembly method. Finally, taking the ISA of antenna as an example, successful application of the proposed dynamics model and controller to the assembly mission was verified. •A dual quaternion dynamics model for the transportation of ISA mission was proposed.•The model considers coupling effects among deformation, translation and rotation of assembling robot.•A PD controller of relative motion is designed based-on the coupling dynamics model.